Modelado computacional del comportamiento de las células madre en un biodispositivo impreso en 3D (2018)
The following document presents the development of an agent based model which simulates the behavior of mesenchymal stem cells (MSC), cardiomyocites and endothelial cells in a 3D-printed biodevice which is implanted on the infarcted myocardium as part of a potential treatment for the regeneration of the affected tissue. Examples of computational modeling applied to the behavior of cells are shown and some 3D bioprinting techniques are explained, such as microextrusion, which is used for the fabrication of the biodevices. The context for which the model has been thought is also described, taking into account the use of 3D printing as fabrication technique and the in vitro tests that would validate the results. After this, some machine learning techniques are presented, given that they were considered as alternatives to develop the model. Following the implementation of an ordinary differential equation-based model, the use of agent based modeling was considered as a tool that would better allow including the cellular microenvironment characteristics in the model. Thus, the development of the model with the software Netlogo, its functioning and the result’s visualization are explained step by step. At last, some results are shown, which were obtained after running determined experiments defined through an experimental design and their analysis, which shows that the model can simulate processes that occur in the cellular microenvironment of the infarcted myocardium through the interactions of cells and that it allows the observation of emergent behaviors that can be helpful to determine the characteristics that favor the success that is expected the treatment with the 3D- printed biodevice.t